2003
DOI: 10.1097/00002508-200307000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Use of Botulinum Toxin in the Treatment of Chronic Myofascial Pain

Abstract: The results of this study are consistent with other studies showing the efficacy of BTX-A for treating pain in MPS. The evaluation of the psychologic dimension of this disorder and its associated disability can provide valuable information for the adequate management of these patients and for assessing treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 38 publications
0
23
0
6
Order By: Relevance
“…A number of open label and retrospective studies have been done to assess the usefulness of BoNTA in treating this condition. The preliminary results were encouraging as Botox was shown to be effective in relieving pain (Lang 2000;De Andrés et al 2003;Wheeler et al 2001a;Royal et al 2001). However, these findings have not been confirmed by RCTs.…”
Section: Msk Pain Disordersmentioning
confidence: 99%
“…A number of open label and retrospective studies have been done to assess the usefulness of BoNTA in treating this condition. The preliminary results were encouraging as Botox was shown to be effective in relieving pain (Lang 2000;De Andrés et al 2003;Wheeler et al 2001a;Royal et al 2001). However, these findings have not been confirmed by RCTs.…”
Section: Msk Pain Disordersmentioning
confidence: 99%
“…In these studies, BT was injected intramuscularly into painful trigger points under electromyographic guidance for neck-shoulder myofascial pain syndromes [25,26,28] while CT or fluoroscopic guidance was utilized for deeper muscles such as iliopsoas, quadratus lumborum or piriformis [5,27]. The encouraging findings of these investigations have led to the use of BT in other syndromes where the specific goal is relief of pain, such as neuropathic pain or temporomandibular dysfunction [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…80 Several other studies have also shown that the administration of botulinum toxin can reduce the activity of trigger points. [81][82][83][84][85][86][87] Therefore, trigger points are found in close vicinity of motor endplates, which are spread out throughout the entire muscle. [88][89][90] Active trigger points are clustered around motor endplates and feature more endplate noise than latent trigger points, which once again supports that active trigger points are more sensitized.…”
mentioning
confidence: 99%